What is early modern history? - Wiesner-Hanks, Merry E. 1952- (Cambridge, [England] Polity Press, 2021)
"A pivotal introduction to early modern history's approaches and methods"--Provided by publisher.
1. Economic and social history -- 2. Religious, intellectual, and cultural history -- 3. Women's, gender, and sexuality studies -- 4. The Atlantic world -- 5. The global early modern -- 6. Popular and public history -- Afterword: The future of early modern history/studies?
Includes bibliographical references and index.
Keywords: History, Modern -- 16th century -- Historiography; History, Modern -- 17th century. -- Historiography; History, Modern -- 18th century -- Historiography; History, Modern -- 16th century; History, Modern -- 17th century; History, Modern -- 18th century